Analisis Efektivitas Pasal 28 Ayat 2 UU ITE Nomor 1 Tahun 2024 dalam Perlindungan Korban Ujaran Kebencian Berbasis Sara di Media Sosial - Chindi Oeliga Yensi Afita; M. Nanda Setiawan; Halida Zia; Mario Agusta; Lara Artifa Putry (Universitas Batanghari Jambi, 2025)
This study analyzes the effectiveness of Article 28 paragraph (2) of Law Number 1 Year 2024 concerning Information and Electronic Transactions (UU ITE) in providing legal protection for victims of hate speech based on ethnicity, religion, race, and inter-group relations (SARA) on social media. Hate speech on social media is increasingly widespread and has the potential to threaten national unity. Although the UU ITE regulation prohibits the dissemination of information that incites hatred based on SARA, its enforcement faces various obstacles such as ambiguous legal norms, low digital literacy, and evidentiary challenges. This study uses a normative juridical approach with case analyses of Meiliana, Jozeph Paul Zhang, and Ahmad Dhani as examples. The findings indicate that victim protection is still inadequate, and law enforcement is not fully effective and fair. Therefore, a collaborative strategy involving the government, law enforcement, social media platforms, and the public is needed to address the spread of hate speech more effectively and justly.